Extrato seco padronizado de Amburana cearensis cultivada e constituintes químicos modulam a inflamação em um novo modelo de asma exacerbada em camundongos BALB/C e a resposta neutrofílica in vitro - Amaral, Hilmara Helia de Sousa (2017)
Asthma is a chronic inflammatory disease that affects more than 300 million people around the world. The main cause of hospitalization and mortality related to the disease are the exacerbations characterized mainly by an inflammatory response profile where Th2, Th17 and neutrophil lymphocytes play an important role in addition to resistance to corticosteroid therapy. This justifies the importance of research on new drugs for the treatment of allergic asthma, especially exacerbation. In this context, medicinal plants such as Amburana cearensis appear as a potential source of new drugs for the treatment of exacerbated allergic asthma. Faced with the risk of extinction of this wild species, in the last years several chemical and pharmacological studies have been carried out generating promising results with cultivated species, which has as active principles coumarin (CM) and vanillic acid (AV). The aim of this study was to investigate the effects of the standardized extract of cultured A. cearensis (ESPACC, markers: CM and AV), CM and AV on exacerbated allergic asthma in BALB / c mice, including the evaluation of these in the neutrophilic response. The pattern of allergic asthma induced by OVA and exacerbated by LPS in BALB / c mice was investigated, investigating different experimental conditions that were evaluated mainly by the analysis of the accumulation of inflammatory cells in the bronchoalveolar lavage (BAL) of the animals. The effects of ESPACC and CM (vo or ip) on the accumulation of inflammatory cells, tissue morphology and levels of IL-4 and TNF-α cytokines in BAL of animals sensitized and challenged with LPS + OVA , in addition to the evaluation of the effects of ESPACC, CM and AV on the degranulation and production of reactive oxygen species (EROS) in PMA-activated neutrophils. In the standardization of the exacerbated asthma model, it was seen that the dose of OVA and LPS, as well as the increase in the duration of exposure to the antigens, were determinant for obtaining the model of exacerbated allergic asthma. Treatment of CM animals (10 or 20 mg / kg, ip or v0, respectively) did not significantly reduce leukocyte accumulation in BAL compared to the control group, but selectively modulated neutrophil migration. ESPACC (100 mg / kg, ip) was able to significantly inhibit leukocyte accumulation in BAL, mucus production and cytokine secretion. In neutrophil culture, ESPACC, CM and AV significantly reduced the neutrophil degranulation induced by PMA measured by the release of MPO, as well as EROS production. The results indicate that cultured A. cearensis, CM and AV have an anti-inflammatory effect in an exacerbated allergic asthma model, modulating inflammatory cell accumulation and neutrophil response, as well as the production of mucus, cytokines and EROS. The results showed that cumaru and its chemical constituents are a potential source for the development of anti-inflammatory drugs to be used in the treatment of exacerbated allergic asthma.